Assessment of listing and categorisation of animal diseases within the framework of the Animal Health Law (Regulation (EU) No 2016/429): bovine genital campylobacteriosis. (12th October 2017) - ; More, Simon; Bøtner, Anette; Butterworth, Andrew; Calistri, Paolo; Depner, Klaus; Edwards, Sandra; Garin‐Bastuji, Bruno; Good, Margaret; Gortázar Schmidt, Christian; Michel, Virginie; Miranda, Miguel Angel; et al.
Abstract: Bovine genital campylobacteriosis has been assessed according to the criteria of the Animal Health Law (AHL), in particular criteria of Article 7 on disease profile and impacts, Article 5 on the eligibility of bovine genital campylobacteriosis to be listed, Article 9 for the categorisation of bovine genital campylobacteriosis according to disease prevention and control rules as in Annex IV and Article 8 on the list of animal species related to bovine genital campylobacteriosis. The assessment has been performed following a methodology composed of information collection and compilation, expert judgement on each criterion at individual and, if no consensus was reached before, also at collective level. The output is composed of the categorical answer, and for the questions where no consensus was reached, the different supporting views are reported. Details on the methodology used for this assessment are explained in a separate opinion. According to the assessment performed, bovine genital campylobacteriosis can be considered eligible to be listed for Union intervention as laid down in Article 5(3) of the AHL. The disease would comply with the criteria as in sections 4 and 5 of Annex IV of the AHL, for the application of the disease prevention and control rules referred to in points (d) and (e) of Article 9(1). The assessment here performed on compliance with the criteria as in section 3 of Annex IV referred to in point (c) of Article 9(1) is inconclusive. The animal species to be listed for bovine genital campylobacteriosis according to Article 8(3) criteria is mainly cattle as susceptible and reservoir.